2008
DOI: 10.1016/j.genm.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the fetal programming of hypertension

Abstract: Background-Numerous clinical and experimental studies support the hypothesis that the intrauterine environment is an important determinant of cardiovascular disease and hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
142
5
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(163 citation statements)
references
References 85 publications
14
142
5
2
Order By: Relevance
“…Many studies have found gender differences in foetal programming of some chronic diseases in animal models. [25][26][27] For example, consistent with our results, a study of pregnant mice revealed a gender-specific effect on foetal programming of blood pressure. 25 With regard to vascular structure, Gariepy et al have suggested possible protection of the female gender from early structural arterial alteration due to smoking, on the basis of the finding that smoking-related increase in intima-media thickness exists only in men, and not in women.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have found gender differences in foetal programming of some chronic diseases in animal models. [25][26][27] For example, consistent with our results, a study of pregnant mice revealed a gender-specific effect on foetal programming of blood pressure. 25 With regard to vascular structure, Gariepy et al have suggested possible protection of the female gender from early structural arterial alteration due to smoking, on the basis of the finding that smoking-related increase in intima-media thickness exists only in men, and not in women.…”
Section: Discussionsupporting
confidence: 91%
“…8 -10 Mechanisms for the programmed gender differences are reviewed elsewhere. 140 These large cohorts also underscore the U-shaped relationship between risk for CKD and birth weight, indicating increased risk with both LBW and HBW. 8,16,115…”
Section: Measures Of Renal Functionmentioning
confidence: 80%
“…Two distinct mechanisms are possibly involved in this paradox: (1) pregnancy weight gain is positively associated with offspring weight or BMI and in turn positively associated with offspring SBP; and (2) pregnancy weight gain is negatively associated with offspring SBP directly or through other pathways, such as disturbing the normal development of fetal organs related to blood pressure control. [32][33][34][35] Both maternal chronic hypertension and preeclampsia-eclampsia were significantly associated with high childhood SBP. Our new findings suggested that neither intrauterine nor childhood growth could explain these associations.…”
Section: E718mentioning
confidence: 98%